Voices - Raak, Kaine-Ene; Kuik, Valentin (Estonia, 1995)
“Voices” is an anthropological examination of the lives of the Khanty people, as seen through the eyes and fate of Yeremey Aipin, a Khanty writer. The filmmaker concentrates on one period of Yeremey Aipin’s life: when he was elected at the last Supreme Soviet and at the first State Duma, and attempted to fight for Western Siberia’s people’s rights from the legislative point of view, at the State level. The filmmaker follows Yeremey Aipin during his third electoral campaign, which led to a failure, for Aipin discovered the day of the vote that his candidature had been invalidated at the last moment.
Soros Documentary Fund